Types and Purposes of Kinayah in the Qur’an - Syam, Ishmatul Karimah; Komarudin, Edi; Taufiq, Wildan (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to examine and explain kinayah, including the meaning, types, function, and purpose in the Qur'an. This research is qualitative by going through library research and research. This study concludes that kinayah is included in one of the balaghah sciences which discusses the meaning of a word not only from the prevalence of its meaning, but also its meaning can be understood with its true meaning. Kinayah also has several types and the distribution of each type. The purpose of the existence of kinayah in the Qur'an, among others, is to remember the greatness of God, beautify words, avoid taboo sentences, and the like. This simple research is expected to benefit and add insight to religious studies, especially in the language field.